(untitled) (Scientia Agropecuaria, 2021)
The soil is considered the largest carbon reservoir in nature after the oceans, its content has been studied mostly in forest ecosystems, leaving aside other important ecosystems such as high Andean natural pastures, whose plant cover is made up of species diversity, which occupy large areas. The objective of the research was to determine the influence of the altitudinal variability on the Soil Organic Carbon (SOC) storage capacity of the Stipa, Festuca and Calamagrostis species, as well as its relationship with the characteristics of the soils. 73 soil samples were extracted at 0.2 m depth, between altitudes of 4000 to 4410 m.a.s.l.; To determine the COS, the wet oxidation methodology was used. The results show that there is no significant difference in the accumulation of SOC of the species studied, its general mean is 364.33 ± 48.80 t ha-1. The correlation coefficients between the amount of SOC and altitude, sand, silt, clay, temperature and organic matter were 0.84; 0.72; -0.30; -0.56; -0.82 and 0.91, respectively. As the altitude increases the COS content increases; the variation of sand and clay in the structure of the soil, influence this process, while low temperatures favor the accumulation of carbon according to the availability of organic matter.